Anaesthetic Considerations in Paediatric Myasthenia Gravis. (25th September 2011) - Masters, Oliver William; Bagshaw, Oliver N.
Abstract : Myasthenia gravis is of particular interest to anaesthetists because of the muscle groups affected, the pharmacology of the neuromuscular junction, and interaction of both the disease and treatment with many anaesthetic drugs. Anaesthetists may encounter children with myasthenia either to facilitate treatment options or to institute mechanical ventilation in the face of a crisis. This paper reviews the literature pertaining to the pathophysiology and applied pharmacology of the disease and explores the relationship between these and the anaesthetic management. In addition to illustrating the tried-and-tested techniques, some newer management options are explored.